2017
DOI: 10.1016/j.applanim.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Flock size during rearing affects pullet behavioural synchrony and spatial clustering

Abstract: Highlights• Behavioural synchrony and clustering in space decreased with increasing bird group size.• Preening was the most synchronised over time and feeding the most clustered in space.• Simultaneous access to resources for all is more important in small than large groups. AbstractAnimals are often synchronised in their behaviour, with costs and benefits varying according to group size and the behaviour being performed. Making decisions about optimal allocation and distribution of resources to animals in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Synchrony within groups can emerge through social facilitation 28 30 , where an individual is more likely to conduct a behaviour when in the presence of another individual that is already engaged in conducting the behaviour. Alternatively, synchrony can result from some external local influence or zeitgeber 31 , 32 causing similar responses to occur in multiple individuals at the same time. Studies that have suggested that synchronisation is induced by local stimuli usually consider behaviours that require individuals to be aggregated at a local resource, such as foraging behaviour seen at a feeder ( e .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synchrony within groups can emerge through social facilitation 28 30 , where an individual is more likely to conduct a behaviour when in the presence of another individual that is already engaged in conducting the behaviour. Alternatively, synchrony can result from some external local influence or zeitgeber 31 , 32 causing similar responses to occur in multiple individuals at the same time. Studies that have suggested that synchronisation is induced by local stimuli usually consider behaviours that require individuals to be aggregated at a local resource, such as foraging behaviour seen at a feeder ( e .…”
Section: Discussionmentioning
confidence: 99%
“…g . 32 34 ). The loafing behaviour we recorded here is less likely to be either clustered or influenced by local stimuli than feeding behaviours, but could conceivably be driven by local habitat differences in predation risk that affect vigilance behaviour, such as exposure and proximity to cover 35 – 39 , as well as position within the group and proximity to other individuals 4 , 6 , 40 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the total number of birds DB (including the focal hen) was counted within each image, and the total number of birds present on the open litter area was counted. Synchrony can be defined as multiple animals in a group performing a behavior simultaneously ( Keeling et al., 2017 ). For this study, we looked at hens DB at the same time on the open litter.…”
Section: Methodsmentioning
confidence: 99%
“…To test the differences in distribution between the expected and the observed number of marked birds, we calculated the distribution index according to the formula by Keeling et al (25): false(N observed marked birds in transect–N expected marked birds in transectfalse)2N expected marked birds in transect The expected number of marked birds/transect was estimated according to the specific transect dimensions. The distribution index tends to be zero when the observed and expected number of marked birds are similar, indicating a random bird distribution.…”
Section: Methodsmentioning
confidence: 99%